Dependence of optical and electrical properties on Ag thickness in TiO2/Ag/TiO2 multilayer films for photovoltaic devices. Issue 6 (July 2015) - Kim, Jun Ho; Lee, Han-Kyeol; Na, Jin-Young; Kim, Sun-Kyung; Yoo, Young-Zo; Seong, Tae-Yeon
Abstract: We report on the formation of highly transparent and low conductance TiO2 /Ag/TiO2 multilayer films with high figure of merit (FOM). The optical and electrical properties of the multilayer films were investigated as a function of Ag layer thickness. As the Ag thickness increased, the transmission window narrowed and the transmittance was gradually lowered. The TiO2 /Ag/TiO2 multilayer films have the highest transmittance of 86.3–97% at 591 nm for different Ag thicknesses. The relationship between transmittance and TiO2 thickness was simulated using the scattering matrix method to understand the abnormally high transmittance. As the Ag thickness increased from 15 to 25 nm, the carrier concentration of the TiO2 /Ag/TiO2 samples gradually increased from 6.18×10 21 to 1.07×10 22  cm −3 and the mobility also increased from 16.7 to 25.2 cm 2 /V-s. Meanwhile, the sheet resistance slightly decreased from 6.17 to 2.27 Ω⧸sq with the Ag thickness. The TiO2 /Ag/TiO2 multilayer (with Ag thicknesses of 17–21 nm) had Haacke׳s FOMs of 121×10 −3 –157.2×10 –3  Ω −1 .